PEMBUATAN RANCANG BANGUN PENERIMAAN SISWA BARU SEBAGAI SARANA PENINGKATAN LAYANAN PADA TK LIYA CIPUNEGARA SURABAYA - Mandita, Fridy; Januantoro, Ardy (Universitas PGRI Yogyakarta, 2023)
Education is a key aspect in improving Human Resources (HR). Education starts at an early age so that future generations are ready to face increasingly fierce and highly competitive competition. Liya Kindergarten (TK) is one of the educational institutions that participates in providing educational services and focuses on early childhood education. The age range of Kindergarten students is expected to be able to meet the competency criteria for entering Elementary School (SD). In providing information services to the public regarding Kindergarten Liya, it is often difficult to provide up-to-date information to the public regarding the acceptance of new students. This information is in the form of information on school activities, registration information, curriculum information and information on education costs. From these problems, the creation of a new student admissions design for schools is expected to be a solution to the problem to assist the process of registering new students. The website can provide services quickly and accurately with simple steps in registering new students. The method used in this community service is interviews with related users at the location of the community service, namely Liya Kindergarten for a certain period of time and at the end of the community service there is training on using the website to build new student acceptance for users. With this website, it is hoped that it can improve the quality of services at Kindergarten Liya to be able to provide accurate information for people who need it. In addition, it can be a means of promotion related to Kindergarten Liya and on the other hand it can increase the school's income. Keywords: Kindergarten, new student admissions, service quality, information system